PENGAMBILAN KEPUTUSAN SEKOLAH MELALUI MANAJEMEN STRATEGIK PADA SEKOLAH MENENGAH PERTAMA - Marzuki, Marzuki (UNIVERSITAS SERAMBI MEKKAH, 2014)
Abstract This study aims to determine the mechanism, consideration, implementation, and dissemination of the principal decision-making through strategic management at Bandar Baru SMPN 1. This research used descriptive method with qualitative approach, data collection techniques were interviews, observation and documentation study. Subjects were principals, vice-principals, and teachers. The results showed that: (1) The mechanism of decision-making is done by identifying activities problems, formulate goals, determine alternatives, determine solutions, and decision-making, (2) consideration in decision-making is done by consensus paths between teachers and employees, (3) Implementation of decision-making implemented through legalization, operational plans, and communication, and action, monitoring, review and evaluation, and (4) socialization of decisions implemented through an open explanation to the vice principal and carried out according to plan. Keywords : strategic management, and decision making